PENGETAHUAN DAN PENERAPAN SASARAN KESELAMATAN PASIEN PADA MAHASISWA SEMESTER 6 DI AKADEMI KEPERAWATAN ADI HUSADA SURABAYA - Iswati Iswati (Adi Husada Nursing Journal, 2015)
Patient safety incident can be done by nursing students when doing clinical practice in hospitals. This happens because of a lack of knowledge about patient safety. The purpose of this study was to identify the relationship between knowledge of patient safety with the implementation of patient safety in the 6th semester student at the Academy of Nursing Adi Husada Surabaya. This type of research is correlational, variable research is knowledge of patient safety and patient safety application. Total population of 143 and the number of samples is 131. The sampling technique is used directly probability sampling type simple random sampling. Measuring instruments used questionnaires and observation sheets. Data analysis using the spearman rank test, (α= 0.05,p=0.01,r= 0.817) indicating Ho refused meaning that there is a relationship between knowledge and application of patient safety. Results of the study recommended the need for the provision of special courses on patient safety for students in the 6th semester nursing Academy Adi Husada Surabaya. Insiden keselamatan pasien dapat dilakukan oleh mahasiswa saat melakukan praktik klinik di rumah sakit. Hal ini terjadi karena kurangnya pengetahuan tentang keselamatan pasien. Tujuan penelitian ini untuk mengidentifikasi hubungan antara pengetahuan tentang keselamatan pasien dengan penerapan keselamatan pasienpadamahasiswa semester 6 di Akademi Keperawatan Adi Husada Surabaya. Jenis penelitian ini adalah korelasional, variable penelitiannya adalah pengetahuan tentang keselamatan pasien dan penerapan keselamatan pasien. Jumlah populasi sebanyak 143 dan jumlah sampel adalah 131. Teknik sampling yang digunakan adalah probability sampling jenis simple random sampling. Alat ukur yang digunakan kuesioner dan lembar observasi. Analisis data menggunakan Spearman Rank Test, (α=0.05, p= 0.01, r=0.817) hal ini menunjukkan Ho ditolak artinya terdapat hubungan antara pengetahuan dan penerapan keselamatan pasien. Hasil penelitian merekomendasikan perlunya pemberian mata kuliah khusus tentang keselamatan pasien bagi mahasiswa semester 6 di Akademi Keperawatan Adi Husada Surabaya. DOWNLOAD FULL TEXT PDF >>